ASSESSMENT OF THE PREGRAVID PREPARATION EFFECTIVENESS IN CASE OF RISK FACTORS FOR SEVERE PRE-ECLAMPSIA - Белинина, Антонина Анатольевна; Ремнева, Ольга Васильевна; Фадеева, Наталья Ильинична; Брусенцов, Иван Григорьевич (Mother and Baby in Kuzbass, 2017)
Goal – to assess the effectiveness of pregravid preparation at women, taking into account the revealed risk factors for severe preeclampsia. Material and methods. The research refers to 208 patients with risk factors for severe pre-eclampsia who were divided into two groups. The main group included 118 women who did not get pregravid preparation and were prematurely delivered (up to 33 weeks of gestation inclusive) due to severe preeclampsia. The comparison group consisted of 90 women who got pregravid preparation in view of risk factors, whose pregnancy was not complicated by severe preeclampsia and ended with delivery in time. Results. Risk factors for severe pre-eclampsia determined during the clinic-laboratory investigation: pre-eclampsia in anamnesis, extragenital pathology (obesity, chronic pyelonephritis, chronic arterial hypertension), combinations of polymorphisms of hemostasis and folate cycle genes, hereditary hypertension, late reproductive age. The average number of risk factors per patient was 2.64. Women who got pregravid preparation in view of risk factors did not have severe preeclampsia, but moderate pre-eclampsia developed in 60 % of cases. It allowed to deliver in time, to reduce the frequency of Cesarean section by 3 times, to avoid perinatal losses and severe damages of newborns’ central nervous system. Conclusion. Pregravid preparation of patients with risk factors for severe preeclampsia allows to reduce heaviness of its clinical manifestations, frequency of abdominal delivery and to avoid adverse perinatal outcomes.